Collection Development Strategy In Dinas Perpustakaan dan Arsip Kabupaten Nias Utara - Hidayatullah Giawa (Pena Cendekia Insani, 2022)
The goal of this research was to determine the collection development strategy and process at the North Nias Regency Library and Archives Service. The researcher used descriptive qualitative research in this study to describe the facts and the nature of the relationship between the phenomena under investigation. The results revealed that the North Nias Regency Library and Archives' collection development strategy had in principle been going well, beginning with the analysis of librarian needs, selection policies, selection processes, procurement, weeding, and evaluation, but at the level of user analysis, selection policies, procurement, weeding, and evaluation, but at the collection development level it had not run optimally in the past year due to several factors. Due to budget constraints, the acquisition of collections, particularly at the North Nias Regency Library and Archives, was halted from January 2020 to February 2021. Meanwhile, student donations, donations, and grants from local government agencies are the primary sources of collection development.